النقد الأدبي الإدراكي وتحوّل مسارات الاشتغال - عباس, علي محمد نور مجيد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
research highlights the major shift that has recently occurred in the course of critical study and the adoption of mental analysis as the starting point for critical studies. There are now standardized functions of language as they occur in the human brain and mind. As a result, there has been a shift in the function of language from communicative and informative to linguistic and cognitive, It has become clear that cognitive analysis in literary discourses has become more general in the issue of criticism and the link between linguistic sciences and cognitive neurosciences?, and thus the focus on the mental processes involved in understanding literature and interpreting the processes of critical analysis, and how do cognitive processes such as perception, memory and attention affect the reading experience?, How do readers create mental representations of the world in relation to reality? How do they attribute beliefs, intentions, and representations to others and give them mental life? How do they study language, describe and explain its methodology, structure, and functions, and how are they achieved through the language system?, Based on these data, the research addresses the problem of cognitive connections in the field of literary criticism, which is considered the core of the unique human cognitive capacity to produce, transmit, and process meaning. Despite the simplicity of this idea, it is powerful in two respects: first, by providing procedures and principles for some phenomena of meaning and reasoning, and second, by providing us with insights into the organization of cognitive fields to which we do not have direct access.